2007
DOI: 10.1002/pmic.200601039
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analytical approach in veal calves administered the anabolic androgenic steroids boldenone and boldione: urine and plasma kinetic profile and changes in plasma protein expression

Abstract: Surveillance of illegal use of steroids hormones in cattle breeding is a key issue to preserve human health. To this purpose, an integrated approach has been developed for the analysis of plasma and urine from calves treated orally with a single dose of a combination of the androgenic steroids boldenone and boldione. A quantitative estimation of steroid hormones was obtained by LC-APCI-Q-MS/MS analysis of plasma and urine samples obtained at various times up to 36 and 24 h after treatment, respectively. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 50 publications
2
24
0
1
Order By: Relevance
“…The presence of these proteins in the blood plasma of cattle was previously shown in our study as well as in the works of other authors (Wait et al 2002, D'Ambrosio et al 2005, Draisci et al 2007, Yang et al 2012.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The presence of these proteins in the blood plasma of cattle was previously shown in our study as well as in the works of other authors (Wait et al 2002, D'Ambrosio et al 2005, Draisci et al 2007, Yang et al 2012.…”
Section: Discussionsupporting
confidence: 90%
“…There have been numerous studies investigating the effects of different factors on plasma proteome changes in cattle; for example, Yang et al (2012) found significant changes in plasma acute phase proteins (APPs) expression, using two-dimensional electrophoresis (2-DE), in cows which had developed post-partum subclinical mastitis. An attempt has also been made to evaluate the functional molecular plasma biomarkers for the detection of growth-promoting substances which are illegally used in veal calves (Draisci et al 2007). In our previous study, the dynamic changes in plasma proteome expression pattern from birth to the seventh day of the life of calves which were fed dams colostrum and milk were observed (Herosimczyk et al 2013).…”
mentioning
confidence: 99%
“…Proteomic tools have also been employed to reveal molecular serum/plasma biomarkers for the detection of growth promoting substances that are illegally used in the veal calves. Recently, two-dimensional electrophoresis (2-DE), matrix-assisted laser desorption/ionisation time of flight mass spectrometry (MALDI-TOF-MS) and liquid chromatography-hybrid ion trap time of flight mass spectrometry (μLC-IT-TOF/MS) have been successfully applied to the global analysis of plasma from calves treated orally with the androgenic steroids such as boldenone and boldione (Draisci et al 2007). Draisci et al (2007) showed that single dose of the boldenone resulted in the overexpression of the N-terminal truncated form of apolipoprotein A-I and thus may be considered as a candidate biomarker for the anabolic androgens treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two-dimensional electrophoresis (2-DE), matrix-assisted laser desorption/ionisation time of flight mass spectrometry (MALDI-TOF-MS) and liquid chromatography-hybrid ion trap time of flight mass spectrometry (μLC-IT-TOF/MS) have been successfully applied to the global analysis of plasma from calves treated orally with the androgenic steroids such as boldenone and boldione (Draisci et al 2007). Draisci et al (2007) showed that single dose of the boldenone resulted in the overexpression of the N-terminal truncated form of apolipoprotein A-I and thus may be considered as a candidate biomarker for the anabolic androgens treatment. Nevertheless, in the available literature there is a lack of information concerning other age-dependent and diet-dependent plasma proteome changes that occur in response to dynamic adaptation processes, during the early postnatal period.…”
Section: Introductionmentioning
confidence: 99%
“…Isoelectrofocusing was conducted using a Multiphor system (GE Healthcare) for the first-dimension analysis, and an Ettan Dalt Six apparatus for SDS-PAGE (GE Healthcare) was used according to the manufacturer’s instructions. Focused strips were equilibrated according to a standard procedure and then applied to 12.5% SDS polyacrylamide gels [18,19]. After staining with colloidal Coomassie blue, the gels were scanned with a 2D image scanner (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%